Patients with cystic fibrosis having a residual function mutation: Data from the Italian registry. Issue 2 (18th December 2018) - Salvatore, Donatello; Padoan, Rita; Buzzetti, Roberto; Amato, Annalisa; Giordani, Barbara; Ferrari, Gianluca; Majo, Fabio
Abstract: Background: CFTR mutations permitting residual function (RF) of the CFTR protein are disease‐causing. These mutations are associated with a pneumopathy that is delayed in onset and is slower in progression than are more common forms of cystic fibrosis (CF), although the disease may become severe in some patients. RF mutations are among the most frequent in Italy, thus encouraging investigation of their prevalence and associated phenotypes. Methods: Data from the Italian Registry were used to compare patients with at least one RF mutation with those homozygous for F508del . Results: A total of 806 patients bearing at least one RF mutation were identified among 5204 registered patients (15.5%). The RF patients were older than the F508de l homozygotes (median age 26.0 years vs 19.8 years, respectively), with a higher median age at diagnosis (6.3 years vs 0.2 years, respectively) and a lower median sweat chloride value (76.0 mmol/L vs 100.0 mmol/L, respectively). In the RF group, lung infections and comorbidities were less prevalent than those in the F508del homozygotes, while better FEV1 and nutritional status were observed at all ages. Within the RF group, RF/ F508del subjects showed more severe pneumopathy than did patients with RF/other mutations. In particular, the 3849  +  10kbC  →  T/F508del subjects had worse FEV1 and a higher prevalence of lung infections than did patients with other genotypes. Conclusions: Patients with RF mutations are numerous in Italy and have a milder disease phenotype than do F508del homozygotes. Inside the RF group, F508del heterozygotes and, in particular, 3849  +  10kbC  →  T/F508del patients showed more severe pneumopathy.